Risk factors of pediatric arterial ischemic stroke; A regional survey - Mohammad Ghofrani; Hassan Tonekaboni; Parvaneh Karimzadeh; Jafar Nasiri; Zahra Pirzadeh; Mohamadreza Ghazzavi; Omid Yghini (International Journal of Preventive Medicine, 2018)
Background: Considering that better understanding of the underlying mechanisms and risk factors of arterial ischemic stroke (AIS) would be helpful for better management of stroke and its outcome in children as well as preventing or reducing the occurrence of its related potential disabilities, the aim of this study was to investigate the most common risk factors and causes of AIS in patients referred to the referral hospitals in Tehran and Isfahan cities of Iran. Methods: In this study, medical files of all pediatric patients admitted to the Mofid and Imam Hossein children's hospitals with the diagnosis of AIS from 2001 to 2011 and 2011 to 2016, respectively, were evaluated. Identified risk factors of AIS were categorized as arteriopathies, cardiac disorders (CDs), infection, acute head-and-neck disorders, acute systemic conditions, chronic systemic conditions, prothrombotic states, chronic head-and-neck disorders, atherosclerosis-related RFs, and others. Results: In this study, 61 patients were evaluated. Mean (standard deviation) age of the patients was 5.1 (3.9) years. About 62.3% of the patients were boys while 37.7% were girls (P < 0.01). A total of 36 patients (59%) had at least one risk factor for AIS. About 40.9% of patients had undetermined risk factors. CDs (21.31%) and vascular disease (21.31%) were the most common risk factors of AIS in the studied children. Nearly 11.5% of the patients had moyamoya vascular disease (MMD). Conclusion: The findings of our study indicated that the most common risk factors for AIS in the two studied regions are congenital heart and vascular diseases. The results of the current study could be used for planning more preventive strategies in patients suffering from the mentioned diseases. In addition, the obtained data could be used for conducting targeted education and management of high-risk patients.